2021
DOI: 10.1088/1361-648x/ac0f2c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interfacial dipole on heterogeneous ice nucleation

Abstract: Heterogeneous ice nucleation is one of the most common and important process in the physical environment. AgI has been proved to be an effective ice nucleating agent in the process of ice nucleation. However, the microscopic mechanism of AgI in heterogeneous ice nucleation has not been fully understood.Molecular dynamics simulations are applied to investigate the ability of which kinds of  -AgI substrate can promote ice nucleation by changing the dipole of  -AgI on the substrate, we conclude that the dipole … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…[28][29][30] However, the lattice template effect was found to be invalid in other materials, such as BaF 2 and CuBr, [31,32] although they also have the similar lattice to ice but are almost not effective to facilitate ice nucleation. Recent studies by Lu et al [33] and Shao et al [20] have shown that the dipole orientation of interfacial water has a vital effect in ice nucleation, which may be responsible for the occasional failure of lattice template effect. The absorption strength of surfaces to water molecules, i.e., the hydrophilicity of surfaces, was also thought to be a key role in affecting the heterogeneous ice nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] However, the lattice template effect was found to be invalid in other materials, such as BaF 2 and CuBr, [31,32] although they also have the similar lattice to ice but are almost not effective to facilitate ice nucleation. Recent studies by Lu et al [33] and Shao et al [20] have shown that the dipole orientation of interfacial water has a vital effect in ice nucleation, which may be responsible for the occasional failure of lattice template effect. The absorption strength of surfaces to water molecules, i.e., the hydrophilicity of surfaces, was also thought to be a key role in affecting the heterogeneous ice nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many simulations and experiments concluded that various properties of substrate, such as hydrophobicity [15,16], surface morphology [17], charge [18], can impact the ice nucleation by altering the behavior of interfacial water molecules (IWs). Lu et al performed a MD simulation to investigate the effect of surface charge on the AgI on ice formation [19]. It was found that, compared with iodide ions exposed surface of AgI substrate, ice nucleation prefers to occur on the surface exposed by silver ions of AgI [20], even though the iodide ion-exposed AgI surfaces also have an almost perfect lattice match with ice crystal.…”
Section: Introductionmentioning
confidence: 99%
“…17 This will cost extra energy to rotate water molecules to the favorable orientation to trigger ice formation. 17,37,40,41 Moreover, the greater dipole−dipole interactions between the surface and interfacial water may restrict the freedom of compensating water molecules required by the growth of ice embryos, resulting in a larger free energy barrier for ice nucleation. 23,41 In summary, we investigate the quantitative structure− activity relationship of alkane chemistry tuning ice nucleation using atomically smooth alkane SAMs as the model surfaces.…”
mentioning
confidence: 99%
“…As shown in the inset of Figure , the stronger surface polarity of the alkane SAM with the longer L can make more interfacial water molecules orientated through inducing the polarization of the interfacial water layer, that is, lead to the higher deviation from the favorable orientation for ice nucleation (i.e., the nonpolarized interfacial water state: the almost equal percentages of water molecules pointing down and up) . This will cost extra energy to rotate water molecules to the favorable orientation to trigger ice formation. ,,, Moreover, the greater dipole–dipole interactions between the surface and interfacial water may restrict the freedom of compensating water molecules required by the growth of ice embryos, resulting in a larger free energy barrier for ice nucleation. , …”
mentioning
confidence: 99%
See 1 more Smart Citation